A new approach for presurgical margin assessment by reflectance confocal microscopy of basal cell carcinoma3. (12th December 2015) - Venturini, M.; Gualdi, G.; Zanca, A.; Lorenzi, L.; Pellacani, G.; Calzavara‐Pinton, P.G.
Summary: Background: Surgical excision represents the most common elective treatment for basal cell carcinoma (BCC). Several noninvasive approaches have been proposed for in vivo determination of tumour margin, in order to achieve radical removal. Objectives: To propose a new approach through the combination of dermoscopy and reflectance confocal microscopy (RCM) for lateral margin detection in BCC. Methods: Ten patients with lesions clinically suggestive of nonpigmented BCCs with ill‐defined margins were enrolled. All BCCs were dermoscopically evaluated first and the ill‐defined margins were marked with a superficial cut and then inspected using RCM. Results: RCM evaluation showed BCC foci beyond the presurgical marker in three out of 10 lesions. Histology confirmed the RCM results: the presence of BCC features across the cut, corresponding to two superficial BCCs and a morpheaform BCC. Conclusions: This new procedure helped to improve the identification of proper margins for surgical excision in nonpigmented BCC with clinically and dermoscopically ill‐defined margins. Abstract : What's already known about this topic? Mohs surgery is considered the most efficient technique for complete removal of basal cell carcinoma (BCC), but it is time consuming and expensive. What does this study add? The suggested procedure of dermoscopy combined with reflectance confocal microscopy helps to improve the identification of proper margins for surgical excision of BCC. Plain language summary available online